Boards engagement in strategy execution : an emerging trend in business strategy research - Muhamad Yusoff, Muhamad Roslan (2015)
The Board assists in creating successful conditions to ensure the alignment of the strategic plan with the organization’s objectives and determines the management’s realistic expectations, risks and opportunities throughout the execution of the strategic plan. The purpose of this study is to evaluate the role of Board management in the strategy execution of the organization. The paper examines the significance of the Board to the development, formulation, and monitoring of the decision-making processes within an organization. Theoretical and empirical data within the literature on relevant aspects of organizational management is described in detail. The research methodology is focused on the qualitative design approach that assisted in exploring, analyzing and evaluating the data obtained with respect to the research topic. The paper analyses numerous peer-reviewed journal articles ranging from past to recent period of time to examine the evolving literature on Board and strategy execution. Published articles from ScienceDirect, Emerald, ProQuest, Swetsnet, EbscoHost and Business Source Premier Databases are explored. The results and findings of the study reveal increased focus of the organizations’ Boards on strategy execution that indicates progress towards a continuous increase in Board involvement. A conflicting situation arises with the fundamentals of agency theory that considers decision-making control as the basic and sole responsibility of the Board of Directors of an organization. The paper also presents certain recommendations that revolve around the formation of a supportive and constructive framework for the organization with regard to Board and management structure and steps towards improving organizational performance.